Inhibitory activity of compounds isolated from Polymnia sonchifolia on aflatoxin production by Aspergillus flavus - Pak, Adriana [UNESP]; Gonçalez, Edlayne; Felicio, Joana D'arc; Pinto, Marina Mori; Rossi, Maria Helena; Simoni, Isabela Cristina; Lopes, Márcia Nasser [UNESP] (Sociedade Brasileira de Microbiologia, 2006)
Polymnia sonchifolia, conhecida como Yacon, e originária da cordilheira dos Andes, sendo muito conhecida devido ao uso de seu tubérculo no controle da Diabetes melitus. Suas folhas podem conter compostos com atividade antifúngica e pesticida, pois não é necessário o uso destes produtos no seu cultivo. Neste trabalho descrevemos a identificação da estrutura química de dois flavonóides isolados das folhas de Polymnia sonchifolia: 3', 5, 7 trihydroxy-3, 4'-dimethoxyflavone (composto 1) e 3',4',5-trihidroxi-7-metoxiflavanona (composto 2) e de duas lactonas sesquiterpenicas: enidrina (composto 3) e uma mistura de enidrina e uvedalina (composto 4), bem como seus efeitos na produção de aflatoxinas por Aspergillus flavus. A identificação dos compostos foi realizada por RMN 13C e ¹H. Todos os compostos foram testados em diversas concentrações em cultura de Aspergillus flavus para avaliar o crescimento e a produção de aflatoxina. O composto 1 na concentração de 15 mig/mL inibiu 25% da produção de aflatoxina B1 (p<0,01). O composto 4 inibiu o crescimento do fungo e a produção da aflatoxina B1 em 34% e 76%, respectivamente. Os resultados mostraram a possibilidade do uso de Polymnia sonchifolia no controle alternativo da producao de aflatoxina B1 pelo fungo Aspergillus flavus.

Polymnia sonchifolia, commonly known as ;yacon;, was originally cultivated at Andes moutains in South America. Recently, the specie attracted worldwide attention because of its wide range of uses, for example in the control of diabetes melitus, besides the antifungal and pesticidal compounds were found in the leaves. This study describes the identification of two flavonoids: 3', 5, 7 trihydroxy-3, 4'-dimethoxyflavone (compound 1) and 3', 4', 5- trihydroxy-7-methoxy flavanone (compound 2) and two sesquiterpenes lactones: enhydrin (compound 3) and a mixture of enhydrin and uvedalin (compound 4) isolated from Polymnia sonchifolia leaves and their effects on the aflatoxin production by Aspergillus flavus. The identification of the compounds were achieved by ¹H and 13C NMR. All compounds were tested in different concentration, to evaluate the growth of Aspergillus flavus culture and the production of aflatoxin. The compound 1, at the concentration 15 mug/mL, inhibited 25% of the aflatoxin B1 production (p<0.01). The compound 4 inhibited 34% and 76% of the fungal growth and AFB1 production respectively. These results show that Polymnia sonchifolia can be used for the development of agents to control aflatoxin B1 production by Aspergillus flavus.
Produção de aflatoxina por Aspergillus flavus é inibida por compostos isolados de Polymnia sonchifolia
Keywords: Polymnia sonchifolia; flavonóides; melampolideos; aflatoxinas; Aspergillus flavus; Polymnia sonchifolia; flavonoids; melampolides; aflatoxin; Aspergillus flavus